Role of the university in regional economic development: the US experience. (20th February 2004) - Premus, Robert; Sanders, Nada; Jain, Ravi K.
Universities have traditionally played a dual role in the nation's innovation system. On the one hand, they enhance the stocks of knowledge and human capital through research and teaching. On the other hand, universities indirectly contribute to innovation in industry and economic growth. In the past few decades, many universities have formally incorporated regional economic development into their mission statements, and in response have spawned impressive growth in university technology transfer mechanisms, such as university-industry research centres, sponsored research, and on-campus licensing and commercialisation activities. These efforts have resulted in a substantial increase in industry support for university research, but the critics argue that selling research for dollars contaminates academic science and shrinks the academic commons. This paper examines evidence that universities contribute to regional economic growth by emphasising strong science research, contributing to human capital investments, and by making the ideas freely available to society. Regions grow when they have the infrastructure and skilled people to absorb the new ideas and turn them into commercial products. University technology transfer initiatives can aid the dissemination and absorption of new knowledge, and thus contribute to economic development, but also they have the potential to shorten time horizons if they place too much emphasis on the profit motive in allocating university resources. The paper concludes that universities need to take strong measures to protect the academic commons by assuring that the funds from commercial activities are used to support the long-term research and teaching missions of the university.